2009
DOI: 10.1038/ajg.2009.282
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Severe Wartime Conditions in Early Life Is Associated With an Increased Risk of Irritable Bowel Syndrome: A Population-Based Cohort Study

Abstract: Our data indicate that exposure to severe wartime conditions in early life is associated with an increased risk of developing IBS. To what extent this is attributable to the stressful environment of war, to severe undernutrition, or to the increased prevalence of infectious diseases is, however, unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 31 publications
0
50
0
2
Order By: Relevance
“…Conversely, psychological factors themselves influence physiological factors, such as the motor, sensory, secretory and immune functions of the gastrointestinal tract (top-down model) (38). Previous studies have shown that early life stressors, such as sexual abuse and maternal separation, are related to the development of IBS (39)(40)(41). Understanding the psychological problems of IBS patients might contribute to the development of effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, psychological factors themselves influence physiological factors, such as the motor, sensory, secretory and immune functions of the gastrointestinal tract (top-down model) (38). Previous studies have shown that early life stressors, such as sexual abuse and maternal separation, are related to the development of IBS (39)(40)(41). Understanding the psychological problems of IBS patients might contribute to the development of effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 For example, in 2009, one retrospective cohort study evaluating the epidemiology of IBS in the World War II period showed that the factor of early life exposure to severe wartime conditions was related with the increase of IBS prevalence. 4 In 2012, Bradford et al 2 found that IBS patients had more EALs such as common trauma, corporal punishment, emotional abuse or sexual assault than healthy subjects. Animal research has played a vital role in advances in the pathophysiology of IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Findings include a weak association of congenital heart defects and ambient temperatures (Agay-Shay et al 2013) and lower levels of cord blood ferritin in mothers exposed to war compared to non-exposed mothers (Armony-Sivan et al 2013). No association was found between exposure to famine and prevalence of irritable bowel syndrome (IBS) (Klooker et al 2009), or between breast cancer and exposure to famine (Painter et al 2006a). Louphaä et al (2000) found a weak association between mid-gestation exposure to famine and a higher prevalence of obstructive airways disease (OR 1.7, 95 % CI 1.1, 2.6), and a study on asthma and exposure to an ice storm found a weak associated in females between high levels of subjective maternal stress and diagnosed asthma (OR 1.09, 95 % CI 1.00, 1.19) (Turcotte-Tremblay and Lim 2014).…”
Section: Resultsmentioning
confidence: 98%